(untitled) (INTERNATIONAL SCIENCE REVIEWS. SOCIAL SCIENCES SERIES, 2024)
The article is devoted to the study of criminological factors for determining the conditions and circumstances of the Commission and concealment of criminal offenses of a terrorist nature, which are determined by the determinants of the formation and development of terrorism as a social and legal phenomenon. The use of criminological analysis to establish causal relations criminal offences of a terrorist nature contributes to a comprehensive, fully disclose the conditions and circumstances preceding the Commission of, conceal these criminal acts, United by a common focus on terrorism, to predict, diagnose conditions and circumstances, the subsequent actions of a criminal nature, to model these factors objectively-subjective nature to analyze the ensuing results and consequences. A systematic approach to identifying factors of a criminal nature and conflict is aimed at establishing incentive and regulatory mechanisms for a specific criminal situation that reveal the direction of criminal offenses of a terrorist nature. The establishment of incentive and regulatory mechanisms for criminal offenses of a terrorist orientation is determined by the analysis of the cause-and-effect relations of the formation and development of terrorism as a social and legal phenomenon.